The impact of the Pandemic on the family context and on the management of teaching work for women - dos Santos Moreira de Carvalho, Aline (Seven Editora, 2023)
This article is about the landscape comprehension using concepts as a tecnic- cientific period and the informational midia and the interfaces between technology and the infraestructures, becoming necessary the review the recent acumulated layers on the landscape. The cultural landscape transforming, the urban landscape layers, processed at the time. This new methologie has an important role for the urban projects future apllications . DOI: 10.56238/pacfdnsv1-120